Kesadaran Hukum Dalam Berlalu Lintas Siswa SMK Zaidar Yahya Kecamatan Rambah - Ryan Prayogi; Ilham Rahmawati (Institut Agama Islam Negeri Ponorogo, 2021)
Indonesia is a developing country where the majority of the population is very much using motorized vehicles, especially vocational students who drive motorized vehicles improperly run red lights, operate cell phones, design their motorbikes that are not in accordance with factory standards and even do not equip themselves with a driving license (This SIM has an impact on traffic law awareness of Zaidar Yahya Vocational School students. So the aim of the study was to determine the level of Traffic Law Awareness of Zaidar Yahya Vocational School Students. While the research method used descriptive qualitative methods. Data collection techniques used observation, interview and documentation techniques. This study shows that the level of traffic law awareness among students of SMK Zaidar Yahya is quite good. This is proven that among these students are only afraid of sanctions when raiding motorized vehicles, do not have a driving license (S IM), and do not use helmets, mirrors etc. Therefore, there is a lack of legal awareness of students in traffic, even though knowledge about traffic has been given, there are still students who commit traffic violations and are not aware of safety and security in driving.